IMPROVING SITUATIONAL AWARENESS IN AIR TRAFFIC MANAGEMENT: A HUMAN FACTORS APPROACH - Akbar, Muhammad Caesar; Munthe, Ridzwan Azmi (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to investigate the influence of human factors in increasing situation awareness in air traffic management. Situation awareness is the ability to understand and respond to existing conditions in a timely manner, especially in the context of complex and dynamic air traffic. Human factors, such as fatigue, experience, and psychological factors, have been known to play an important role in situational awareness. This research uses a qualitative approach with a focus on in-depth interviews with air traffic managers and analysis of human factors involved in events or incidents related to situation awareness. Data will be analyzed using thematic methods to identify patterns, themes and key aspects that influence situation awareness. The research results are expected to provide in-depth insight into the human factors that influence situation awareness in air traffic management, as well as recommendations for improving training, standard operating procedures, and policies to improve response and performance in demanding situations. The conclusions of this research are expected to make a significant contribution to the field of aviation safety and air traffic management as a whole.